1989
DOI: 10.1080/07055900.1989.9649350
|View full text |Cite
|
Sign up to set email alerts
|

The objective analysis of daily rainfall by distance weighting schemes on a Mesoscale grid

Abstract: The authors studied the error of spatial interpolation in the context of a climatic data gridding project (CLI-GRID). Four objective analysis (QA) techniques were implemented: the empirical techniques of Barnes, Cressman and Shepard, and a Gandin-based statistical technique. These were applied to the interpolation of irregularly distributed daily rainfall data. Spatial resolution of the interpolated arrays was 0.05 degree of latitude by 0.05 degree of longitude.In this experiment, radar rainfall patterns serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 9 publications
1
44
0
1
Order By: Relevance
“…In an inter-comparison study of four different interpolation schemes (Bussieres and Hogg, 1989), it was the best of the empirical schemes and performed almost as well as optimum interpolation. Hofstra et al (2008) confirm this finding for the precipitation parameter when comparing two angular distance weighting methods against four other interpolation methods including global and local kriging.…”
Section: Interpolation Of Gauge Data Onto Regular Grid Pointsmentioning
confidence: 94%
See 1 more Smart Citation
“…In an inter-comparison study of four different interpolation schemes (Bussieres and Hogg, 1989), it was the best of the empirical schemes and performed almost as well as optimum interpolation. Hofstra et al (2008) confirm this finding for the precipitation parameter when comparing two angular distance weighting methods against four other interpolation methods including global and local kriging.…”
Section: Interpolation Of Gauge Data Onto Regular Grid Pointsmentioning
confidence: 94%
“…This choice was made in 1991 following external studies (Legates, 1987;Bussieres and Hogg, 1989) and internal inter-comparison studies (Rudolf et al, , 1994 indicating the SPHEREMAP method of being particularly suitable for the analysis of a global precipitation climatology.…”
Section: Interpolation Of Gauge Data Onto Regular Grid Pointsmentioning
confidence: 99%
“…This objective technique has recently been applied by Xie et al (2007) to compute gridded daily precipitation over East Asia and is also being used in the operational MESAN system. OI has been found to outperform other objective techniques for precipitation at the global scale and also at a finer scale in studies in Canada (Bussières and Hogg, 1989) and in France over the Cévennes area, a region with very high spatial and temporal variability (Creutin and Obled, 1982).…”
Section: Analysis Systemmentioning
confidence: 99%
“…After considering several techniques, an inverse-distance weighted method, based on Shepard's (1968) method, was selected (Willmott et al, 1985) that properly accounts for the spatial distribution of the observed data and allows for the extrapolation of peaks and valleys. This technique is advantageous, in that it overcomes several significant limitations of traditional weighted-average approaches, accounts for the sphericity of the Earth, and is among the most reliable techniques for interpolating daily precipitation totals (Bussieres and Hogg, 1989).…”
Section: Meteorological Inputs and Spatial Interpolation Of Datamentioning
confidence: 99%